COINS OF SHAH JAHAN : CREATIONS OF AN ARCHITECT - ANDREW V LIDDLE (NEW DELHI MANOHAR, 2017)
Last of the amazing trilogy on the first three great Mughals.This book deals with the copper, silver and gold coins of Emperor Shah Jahan.
Keywords: NUMISMATICS; COINS; MUGHAL EMPIRE; EMPEROR SHAH JAHAN